Digital Street Culture Decoded: Why criminalizing drill music is Street Illiterate and Counterproductive - Ilan, Jonathan (The British journal of criminology, 2020)
Authorities in the United Kingdom censure ‘drill rap’, the artistic expression of disadvantaged urban youth, citing its connections to serious violence. This is shown to be based on a thin, ‘street-illiterate’ understanding of the genre that ultimately rests on stereotypes of young black men as violent ‘gang’ members. In place of this misreading, a street-literate interpretation of drill is offered from a deep and nuanced analysis of YouTube videos and below the line discussions. It is demonstrated that it is inaccurate and unhelpful to view drill videos as evidence of violent crime or as attempts to glorify or precipitate it. Instead, the stylized videos and violent lyricism are shown to be forms of artistic performance that reveal an ambiguous relationship to criminality. Marginalizing the excluded further, video removals and restrictions on performance are shown to be counterproductive from a crime-reduction perspective. New developments in technology and culture can take shape around existing patterns of criminalization.